2006
DOI: 10.1590/s0100-879x2006000700005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polymorphisms of the MTHFR and APOE genes on susceptibility to diabetes and severity of diabetic retinopathy in Brazilian patients

Abstract: Diabetes mellitus (DM) is a highly prevalent complex genetic disorder. There has been a worldwide effort in the identification of susceptibility genes for DM and its complications, and the 5-10-methylenetetrahydrofolate reductase (MTHFR) and apolipoprotein-E (APOE) genes have been considered good candidate susceptibility genes to this condition. The objectives of the present study were to determine if the 677T MTHFR and ε2/ε3/ε4 APOE alleles are risk factors for DM and for severity of diabetic retinopathy (DR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 37 publications
1
34
0
4
Order By: Relevance
“…To our knowledge, there is only one study (Errera et al 2006) that reported a higher frequency of E2 allele in the small number of male and female diabetic patients (type 1 and type 2) of African-Brazilian and European-Brazilian origins (Errera et al 2006). Unfortunately, this study (Errera et al 2006) did not evaluate the effects of sex and age in order to confirm the association between E2 allele and diabetes. Although E2 might be protective against the development of AD (Farrer et al 1997), it could be detrimental for T2D.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there is only one study (Errera et al 2006) that reported a higher frequency of E2 allele in the small number of male and female diabetic patients (type 1 and type 2) of African-Brazilian and European-Brazilian origins (Errera et al 2006). Unfortunately, this study (Errera et al 2006) did not evaluate the effects of sex and age in order to confirm the association between E2 allele and diabetes. Although E2 might be protective against the development of AD (Farrer et al 1997), it could be detrimental for T2D.…”
Section: Discussionmentioning
confidence: 99%
“…The control group was provided by the Biobank of our institute, and consisted of 401 individuals (336 individuals ascertained in São Paulo and 65 from Fortaleza-CE, as detailed in Errera et al [2006] and Orabona et al [2009], respectively). Ethical issues prevented the collection of control samples in other locations.…”
Section: Materials and Methods Patients And Controlsmentioning
confidence: 99%
“…Among them, 443 were EA (Portuguese, Spanish, Italian, and German) descendants and 124 AfA (West Africa, Angola, Mozambique) descendents (11,12). Patients were evaluated using a questionnaire, physical examination and laboratory tests.…”
Section: Adipor1 Snps In Brazilian Populations Of Different Ancestrymentioning
confidence: 99%
“…The reference group (control) consisted of 190 healthy DM2-free blood donor volunteers at HC-USP (96 EA and 94 AfA, age: 48.28 ± 16.39 years), who were previously described by Errera et al (11,12). The main clinical and laboratory data are reported in Table 1 and were obtained as recommended previously (11,12). A group of 439 non-diabetic quilombo remnant individuals was also included.…”
Section: Adipor1 Snps In Brazilian Populations Of Different Ancestrymentioning
confidence: 99%